Thyristor voltage regulator control algorithm research - Asabin, A A; Kralin, A A; Kryukov, E V (IOP conference series. Materials Science and Engineering, 2019)
The article deals with the development and research of thyristor voltage regulator (TVR) dual-zone control algorithm in the electrical distribution networks 6-20 kV. The TVR control system hardware and software complex based on the algorithm was developed using LabVIEW and NI myRIO controllers. The transverse, longitudinal and longitudinal-transversal voltage regulation modes experimental research was conducted by the TVR prototype. The experimental research results confirmed the developed algorithm and its program realization effectiveness and efficiency.